A co-crystal between benzene and ethane: a potential evaporite material for Saturn's moon Titan. (2016) - Maynard-Casely, Helen E.; Hodyss, Robert; Cable, Morgan L.; Vu, Tuan Hoang; Rahm, Martin
No abstract available